Análise de índices de desconforto ambiental ootdoor: Campus Central da UFRN, Natal - Araújo, Edival (2024)
This study aimed to characterize environmental discomfort in an outdoor environment at the, located on the Central Campus of the Federal University of Rio Grande do Norte (UFRN), during the dry season. Specifically, the study sought to quantify meteorological variables (air temperature, relative humidity, and wind speed) at different times of the day and characterize their diurnal variations, observing potential similarities and differences. Data were collected from December 6 to 14, 2023, at two distinct points, 20 meters apart, during three periods: morning (09:00–09:30), noon (12:00–12:30), and afternoon (17:00–17:30). Measurements were taken every five minutes using KR825 digital thermo-hygrometer-anemometers. Instrument calibration was performed through simultaneous data collection with INMET equipment, located at the UFRN climatological station, from October 31 to November 1, 2023, at 10-minute intervals, establishing adjustment equations via linear correlations. To evaluate thermal comfort, three indices were employed: the Temperature and Humidity Index (ITU), the Thermal Discomfort Index (IDT), and the Effective Temperature with Wind Index (TEv). Descriptive statistical tools such as mean, median, and standard deviation were used in data analysis. Results indicated that point TH3 presented higher relative humidity, while point TH4 recorded higher temperatures. The ITU index did not show variability in comfort levels, suggesting the need for recalibration or replacement of the index. Conversely, the IDT and TEv indices identified different conditions of environmental discomfort, showing that TH4 offered better thermal comfort conditions compared to TH3. It is concluded that instrument calibration and the application of the IDT and TEv indices were effective in characterizing environmental discomfort in the studied area. Point TH4 presented better thermal comfort conditions than TH3, while the ITU was deemed unsuitable for evaluating the environment. It is suggested that the ITU index be recalibrated or replaced in future studies.